Directional Pattern Based Circular Array Interferometer Direction Finding Technique for Phase Interference Avoidance - Kang, Jong Jin; Kim, Jae Hyun (Journal of Korean Institute of Communications and Information Sciences, 2022)
Interferometer direction finding system estimates the direction of arrival by comparing the phase difference of the received signals. To improve probability of interception, circular array antenna structure is usually applied for covering in all directions. Conventional direction finding system is used omni-directional dipole elements but phase interference occurs due to the antenna geometric structure and thus direction finding accuracy is degraded. In this paper, we propose interference avoidance technique which use directional spiral antenna to configure circular array and applying weight value to amplitude ratio of received signal to remove ambiguity of phase differences. By applying proposed technique, a digital direction finding system is implemented and conduct performance verification by measuring the real radar pulse signal. Through the measurement result, proposed technique obtained a high direction finding accuracy of less than RMS 1° only using 5 antenna and receiving channels in the broadband frequency range. This technique can be widely applied to the field of precision direction finding applications against radar and communication signals.
Keywords: Amplitude Ratio; Circular Array; Direction Finding; Interferometer; Phase Interference